Review of Universal Human Rights Theory in the Perspective of Law and Justice - Misdin Arifin HM; Sabna Anggraini (AT-TAFAHUM: Journal of Law, 2025)
This study analyzes the conceptual framework and philosophical foundations of human rights (HAM) through a review of key legal theories. The discussion begins with natural law theory, which argues that human rights are inherent, universal, and derived from transcendental ethical principles as a guide for positive law. As an antithesis, this study presents the theory of legal positivism, which emphasizes that human rights are a formal product of state institutions, where legal validity is separate from moral considerations. Next, this study examines theories of justice, particularly John Rawls's concept of "justice as fairness," to analyze the equitable distribution of rights, obligations, and resources within a social structure. The theoretical analysis concludes with a debate between universalism and cultural relativism. Universalism asserts the global applicability of human rights to every individual, while cultural relativism emphasizes the importance of social context, traditions, and local values. By synthesizing these perspectives, this study concludes that a thorough understanding of these theories is crucial for implementing human rights globally while maintaining sensitivity to the diversity of global contexts.